Manufacturing method of powder for dust core
By forming an insulating layer around soft magnetic powder under controlled temperature conditions, the method addresses the need for low coercivity and low iron loss in porcelain powder, improving magnetic properties for electronic devices.
Patent Information
- Application Number
- JP2022127746
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-08-10
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2042-08-10
AI Technical Summary
The demand for miniaturization and high performance in electronic devices has increased, necessitating porcelain powder with low coercivity and low iron loss to improve energy efficiency and reduce environmental impact.
A method for producing porcelain powder involves forming an insulating layer around soft magnetic powder using a lubricant and insulating resin, adhering to specific temperature conditions defined by equations (1) and (2) to balance high permeability and low hysteresis loss.
This method achieves a balance between high permeability and low iron loss, enhancing the magnetic properties of porcelain powder for use in electronic devices.
Smart Images

Figure 0007623327000012 
Figure 0007623327000001 
Figure 0007623327000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing powder for dust cores. [Background technology]
[0002] Coil components such as reactors are used in a variety of applications, including office equipment, solar power generation systems, and automobiles. Coil components have a coil attached to a core, and this core is made of a powder magnetic core.
[0003] Powder cores are made by compressing powder for powder cores, which contains soft magnetic powder, under high pressure of several tons to several tens of tons to produce a powder compact. This powder compact is then subjected to a heat treatment called annealing to produce a powder core. Examples of soft magnetic powder include FeSiAl alloys, which are made by adding Si and Al to Fe, and an insulating layer made of insulating resin is formed around the soft magnetic powder.
[0004] Due to requirements for improved energy exchange efficiency and low heat generation, powder magnetic cores are required to have magnetic properties that allow a large magnetic flux density to be obtained with a small applied magnetic field, and that minimize energy loss when the magnetic flux density changes. An example of a magnetic property related to magnetic flux density is magnetic permeability. An example of a magnetic property related to energy loss is iron loss (Pcv), also known as core loss. Iron loss (Pcv) is expressed as the sum of hysteresis loss (Ph) and eddy current loss (Pe). [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2000-030925 A Summary of the Invention [Problem to be solved by the invention]
[0006] In recent years, there has been an increasing demand for smaller, more powerful electronic devices, and measures to combat global environmental issues are becoming an urgent priority. As a result, there is an increasing demand for high permeability and low core loss in the powder cores and powders for powder cores that make up coil components.
[0007] The present invention has been made to solve the above-mentioned problems, and an object of the present invention is to provide a method for producing powder for dust cores that can achieve both high magnetic permeability and low iron loss. [Means for solving the problem]
[0008] In order to achieve the above object, the method for producing a powder for dust core of the present invention includes an insulating layer forming step of adding a lubricant and an insulating resin to a soft magnetic powder to form an insulating layer around the soft magnetic powder, The insulating layer forming step includes a lubricant adding step of adding the lubricant to the soft magnetic powder, and a coating step of adding an insulating resin to the soft magnetic powder that has been subjected to the lubricant adding step, drying the resulting mixture, and forming an insulating layer around the soft magnetic powder. The lubricant satisfies the following formulas (1) and (2), where Td (K) is the absolute temperature at which decomposition of the lubricant begins in a thermogravimetric differential thermal analysis, Th (K) is the upper absolute temperature of the drying temperature of the insulating resin in the insulating layer forming step, and Tl (K) is the lower absolute temperature of the drying temperature of the insulating resin in the insulating layer forming step: The upper limit absolute temperature Th and the lower limit absolute temperature Tl of the drying temperature of the insulating resin are set so that the magnetic permeability is 142 or more and the hysteresis loss is 190 (kW / m 3 ) The following is satisfied: The drying temperature in the insulating layer forming step is characterized in that it is equal to or higher than the lower limit of Tl(K) and equal to or lower than the upper limit of Th(K) calculated from the following formulas (1) and (2). (Formula 1) TIFF0007623327000001.tif21145 (Formula 2) TIFF0007623327000002.tif18145
[0009] The insulating layer forming process may include a lubricant adding process of adding the lubricant to the soft magnetic powder, and a coating process of adding an insulating resin to the soft magnetic powder that has undergone the lubricant adding process, drying the resulting powder, and forming an insulating layer around the soft magnetic powder. Effect of the Invention
[0010] According to the present invention, it is possible to achieve both high magnetic permeability and low core loss. [Brief description of the drawings]
[0011] [Figure 1] 1 is a graph showing the ranges of relational expressions (1) and (2). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] (Embodiment) The powder for dust core and the dust core according to the present embodiment will be described in detail below. Note that the present invention is not limited to the embodiment described below.
[0013] Powder cores are magnetic materials used in the cores of coil components installed in office equipment, solar power generation systems, automobiles, etc. Powder cores are made by compressing powder for powder cores and annealing it. Powder for powder cores includes soft magnetic powder. A lubricant is added to the soft magnetic powder, and an insulating layer made of an insulating material is formed. The soft magnetic powder covered with this insulating layer is pressure-molded to make a powder compact, which is then annealed to make a powder core.
[0014] The soft magnetic powder is mainly composed of iron. Examples of the soft magnetic powder include permalloy (Fe-Ni alloy) mainly composed of iron, Si-containing iron alloy (Fe-Si alloy), sendust alloy (Fe-Si-Al alloy), or a mixture of two or more of these powders. The soft magnetic powder may be an amorphous alloy or a nanocrystalline alloy powder.
[0015] When using permalloy (Fe-Ni alloy), the ratio of Fe to Ni is preferably 50:50 or 25:75, but other ratios are also acceptable. For example, Fe-80Ni or Fe-36Ni may be used. In addition to Fe and Ni, Si, Cr, Mo, Cu, Nb, Ta, etc. may be included. Si-containing iron alloys may contain Co, Al, Cr, or Mn.
[0016] Examples of the Fe-Si alloy powder include Fe-3.5%Si alloy powder and Fe-5.5%Si alloy powder, but the ratio of Si to Fe may be other than 3.5% or 5.5%. The Fe-Si-Al alloy is a ternary alloy made of iron, silicon, and aluminum, and contains, for example, about 6 wt% to 10 wt% Si and about 4 wt% to 5 wt% Al relative to Fe, but may also contain about 1 wt% to 3 wt% Ni relative to Fe, and may further contain Co, Cr, or Mn.
[0017] This soft magnetic powder may be produced by a pulverization method or an atomization method. In the pulverization method, a lump of soft magnetic powder is mechanically pulverized. If the lump of soft magnetic powder is large, it is pulverized by a jaw crusher, a hammer mill, a stamp mill, or the like, and if the lump of soft magnetic powder is small, it is pulverized by a ball mill, a vibration mill, or the like. In addition, the atomization method may be any of a water atomization method, a gas atomization method, and a water gas atomization method. For example, in the gas atomization method, gas is blown onto soft magnetic powder melted at high temperature to pulverize it, and then it is cooled and solidified.
[0018] The soft magnetic powder may be subjected to a powder heat treatment process. The powder heat treatment process is a process for heat treating the soft magnetic powder. In the powder heat treatment process, the powder is heated in a non-oxidizing atmosphere for 1 to 6 hours. The non-oxidizing atmosphere includes a low oxygen atmosphere such as 0.01% in the atmosphere or an inert gas atmosphere. Examples of the inert gas include H2 and N2. The heat treatment temperature is 400°C or higher and 800°C or lower.
[0019] Next, a first lubricant adding step is performed. The first lubricant adding step is a step of adding a first lubricant to the soft magnetic powder. This first lubricant adding step corresponds to the lubricant adding step described in claim 1.
[0020] As the first lubricant, one that satisfies the following relations (1) and (2) can be used. (Relationship (1)) TIFF0007623327000003.tif21145(Relationship (2)) TIFF0007623327000004.tif18145
[0021] In the above relational expressions (1) and (2), Td(K) is the absolute temperature at which decomposition of the lubricant begins in a thermogravimetric differential thermal analysis (hereinafter also referred to as the "decomposition onset temperature"). Th(K) is the upper absolute temperature of the drying temperature for the insulating resin in the coating process described below (hereinafter also referred to as the "upper drying temperature"), and Tl(K) is the lower absolute temperature of the drying temperature for the insulating resin in the coating process (hereinafter also referred to as the "lower drying temperature").
[0022] The decomposition start temperature of the lubricant is, for example, the temperature at which the lubricant starts to thermally decompose in a thermogravimetric differential thermal analyzer. The upper limit drying temperature refers to the critical point of the upper limit drying temperature of the insulating resin, and the lower limit drying temperature refers to the critical point of the lower limit drying temperature of the insulating resin. Each critical point was derived from the characteristics in Table 2 of the examples described later.
[0023] After the first lubricant addition step, the soft magnetic powder undergoes a coating step. The coating step is a step in which an insulating resin is added to the soft magnetic powder that has undergone the first lubricant addition step, and an insulating layer is formed around the soft magnetic powder. That is, an insulating layer made of insulating resin is formed around the soft magnetic powder. As long as the insulating layer is formed around the soft magnetic powder, the manner of attachment of the insulating resin does not matter. That is, the insulating resin may be attached so as to cover the entire periphery of the soft magnetic powder, or may be attached so as to cover a part of the soft magnetic powder, with a part of the surface of the soft magnetic powder being exposed. In addition, the insulating resin may be attached to the surface of each particle of the soft magnetic powder, or may be attached to the surface of an aggregate of the soft magnetic powder, or may be attached so that these attachment modes are mixed.
[0024] The insulating resin may be a silane compound, a silicone resin, a silicone oligomer, or a mixture thereof. The insulating layer may be a single layer or multiple layers. For example, the insulating layer may be composed of multiple layers divided into layers according to type, or may be a single layer of one type or a mixture of two or more types of insulating materials.
[0025] The silane compound includes a silane compound without a functional group and a silane coupling agent. As the silane compound without a functional group, for example, an alkoxysilane such as an ethoxy type or a methoxy type can be used, and tetraethoxysilane is particularly preferred. As the silane coupling agent, an aminosilane type, an epoxysilane type, or an isocyanurate type silane coupling agent can be used, and 3-aminopropyltriethoxysilane, 3-glycidoxypropyltrimethoxysilane, or tris-(3-trimethoxysilylpropyl)isocyanurate is particularly preferred.
[0026] The amount of the silane compound added is preferably 0.05 wt% or more and 1.0 wt% or less of the soft magnetic powder. By setting the amount of the silane compound added in this range, the fluidity of the soft magnetic powder can be improved, and the density, magnetic properties, and strength properties of the compacted powder core can be improved.
[0027] Silicone resin is a resin that has a siloxane bond (Si-O-Si) as its main skeleton. By using silicone resin, it is possible to form a coating with excellent flexibility. Silicone resin can be methyl-based, methylphenyl-based, propylphenyl-based, epoxy resin-modified, alkyd resin-modified, polyester resin-modified, rubber-based, etc. Among these, when using methylphenyl-based silicone resin in particular, it is possible to form an insulating layer with little loss on heating and excellent heat resistance.
[0028] The amount of silicone resin added is preferably 0.6wt% or more and 2.5wt% or less relative to the soft magnetic powder. If the amount added is less than 0.6wt%, it will not function as an insulating layer, and eddy current loss will increase, resulting in reduced magnetic properties. If the amount added is more than 2.5wt%, it will result in a reduction in the density of the powder magnetic core.
[0029] As the silicone oligomer, methyl-based or methylphenyl-based ones having an alkoxysilyl group and no reactive functional group, epoxy-based, epoxymethyl-based, mercapto-based, mercaptomethyl-based, acrylic methyl-based, methacrylic methyl-based, vinylphenyl-based ones having an alkoxysilyl group and a reactive functional group, or alicyclic epoxy-based ones having a reactive functional group instead of an alkoxysilyl group, etc. can be used. In particular, by using a methyl-based or methylphenyl-based silicone oligomer, a thick and hard insulating layer can be formed. In addition, in consideration of the ease of forming the insulating layer, a methyl-based or methylphenyl-based one having a relatively low viscosity may be used.
[0030] The amount of silicone oligomer added is preferably 0.1 wt% or more and 2.0 wt% or less of the soft magnetic powder. If the amount added is less than 0.1 wt%, it will not function as an insulating layer, and eddy current loss will increase, resulting in reduced magnetic properties. If the amount added is more than 2.0 wt%, it will result in a decrease in the density of the powder magnetic core.
[0031] In this coating process, insulating resin is added to the soft magnetic powder, mixed, and then heated and dried. By heating and drying the insulating resin, an insulating layer is formed on the surface of the soft magnetic powder. The heating and drying temperature is equal to or higher than the lower limit of Tl (K) and equal to or lower than the upper limit of Th (K) calculated from the relational expressions (1) and (2). By keeping the heating temperature within this range, it is possible to improve the magnetic permeability and reduce the hysteresis loss.
[0032] Although this is a conjecture and the present invention is not limited to this mechanism, it is surmised that by using a lubricant that satisfies the above relational expressions (1) and (2) and drying the insulating resin at a drying temperature that is equal to or higher than the lower limit of Tl (K) and equal to or lower than the upper limit of Th (K), the lubricating action of the lubricant is more effective, the movement of the soft magnetic powder becomes smoother, the particles are closer to each other, and the density is improved, resulting in the realization of both high magnetic permeability and low hysteresis loss.
[0033] In this embodiment, the lubricant adding step of adding the first lubricant is followed by the coating step of adding the insulating resin, but the timing of adding the first lubricant and the insulating resin is not limited to this. That is, the first lubricant adding step and the coating step may be combined into one insulating layer forming step, and the first lubricant and the insulating resin may be added at the same time. Alternatively, the insulating resin may be added first, and then the first lubricant may be added, followed by heating and drying.
[0034] After the coating process, the second lubricant addition process is performed. The second lubricant addition process is a process in which a second lubricant is added to the soft magnetic powder on which the insulating layer is formed. The second lubricant may be the same type as the first lubricant, but it is not necessary to use the same lubricant. In other words, the second lubricant may be a different type from the first lubricant. Also, the second lubricant may be a type that does not satisfy the relational expressions (1) and (2). The amount of the second lubricant added is preferably 0.2 wt% or more and 0.7 wt% or less with respect to the soft magnetic powder.
[0035] After the second lubricant addition step, the pressure forming step is performed. The pressure forming step is a step of producing a green compact by pressure forming the soft magnetic powder on which the insulating layer has been formed. First, the soft magnetic powder is filled into a die, and then, the soft magnetic powder is pressed at a pressure of 10 to 20 ton / cm. 2 In this manner, a powder compact is produced.
[0036] After the pressure molding process, an annealing process is performed. The annealing process is a process in which the powder compact produced through the pressure molding process is annealed to remove distortion in the soft magnetic powder. In the annealing process, the powder compact is heat-treated in a non-oxidizing atmosphere such as nitrogen gas, hydrogen gas, a mixture of nitrogen and hydrogen gas, or a low-oxygen atmosphere of about 0.01%, at a temperature of 650°C or higher and lower than the temperature at which the insulating layer formed around the soft magnetic powder is destroyed (for example, 900°C). By performing this annealing process, a powder magnetic core is produced.
[0037] (Example) The present invention will be described in more detail with reference to examples, but the present invention is not limited to the following examples.
[0038] Powders for dust cores of Examples 1 to 12 and Comparative Examples 1 to 19 were prepared as follows, and dust cores were produced using these powders for dust cores. Examples 1 to 12 and Comparative Examples 1 to 19 differ only in the type of first lubricant and the drying temperature in the coating step, and the other manufacturing steps and conditions are the same.
[0039] First, Fe-Si-Al alloy powder was used as the soft magnetic powder. The Fe-Si-Al alloy powder was heat-treated. The heat treatment was performed in a nitrogen atmosphere at 650°C for 2 hours. The heat-treated Fe-Si-Al alloy powder was mixed with 0.3 wt% of the first lubricant of the type shown in the table below.
[0040] As the first lubricant, five types were prepared: lauric acid, stearic acid, a fatty acid derivative, zinc stearate, and ethylene bisstearamide, as shown in Table 1. The decomposition start temperature, upper limit drying temperature, and lower limit drying temperature of each lubricant are as shown in Table 1. The decomposition start temperature was measured using a thermogravimetric differential thermal analyzer STA7200RV (Hitachi High-Tech Science Corporation) by placing 3 to 7 mg of the lubricant to be measured in a cylindrical container with a diameter of 5.2 mm and a height of 2.5 mm in a nitrogen atmosphere at an atmospheric temperature rise rate of 10°C / min.
[0041] In addition, the upper limit drying temperature and the lower limit drying temperature of the insulating resin were calculated. The upper limit drying temperature is the upper limit critical point of the drying temperature derived from the result of changing the drying temperature of the insulating resin for each lubricant. The lower limit drying temperature is the lower limit critical point of the drying temperature derived from the result of changing the drying temperature of the insulating resin for each lubricant. Specifically, from the results of Table 2 described later, the lower limit critical point in the range where the permeability is 142 or more and the hysteresis loss is reduced was set as the lower limit of the drying temperature, and the upper limit critical point was set as the upper limit of the drying temperature. The upper limit and lower limit of the drying temperature, which are Celsius temperatures, are converted into absolute temperatures to become the upper limit drying temperature Th (K) and the lower limit drying temperature Tl (K) in Table 1.
[0042] For example, in the case of lauric acid, the magnetic permeability is high at 142 or more in the drying temperature range of 50°C to 150°C, and the hysteresis loss is 190 (kW / m 3 ), with the lower limit drying temperature being 50°C and the upper limit drying temperature being 150°C. If these Celsius temperatures of 50°C and 150°C are converted to absolute temperatures, the upper limit drying temperature Th shown in Table 1 below becomes 423.15 (K) and the lower limit drying temperature can be derived as 323.15 (K). For other lubricants, the upper limit drying temperature Th, which is the upper critical point, and the lower limit drying temperature Tl, which is the lower critical point, were calculated in the same manner from the magnetic permeability and hysteresis loss.
[0043] [Table 1]
[0044] After adding the first lubricant, 0.3 wt% of a silane coupling agent and 1.2 wt% of a silicone resin were added as insulating resin to the Fe-Si-Al alloy powder, mixed, and dried for 2 hours. The drying temperature for each sample is shown in Table 2. As a result, an insulating layer of a mixture of the silane coupling agent and the silicone resin was formed around the Fe-Si-Al alloy powder.
[0045] After drying, the mixture was passed through a sieve with 850 μm openings to remove any agglomerations, and a second lubricant was added and mixed. The second lubricant was the same type as the first lubricant for each sample. The second lubricant was added at 0.2 wt% to the Fe-Si-Al alloy powder.
[0046] The Fe-Si-Al alloy powder with the second lubricant added was filled into the die at 15 ton / cm 2 The powder compact was then annealed at 700° C. in a nitrogen atmosphere for 2 hours to produce each powder core.
[0047] The initial permeability at 0 A / m and the hysteresis loss (kW / m 3 ), eddy current loss (kW / m 3 ) and iron loss (kW / m 3 ) was measured.
[0048] When measuring each magnetic permeability, a copper wire with a diameter of 0.5 mm was wound 30 turns around the powder magnetic core as the primary winding.The initial magnetic permeability was calculated from the inductance of the magnetic field strength at 100 kHz and 1.0 V using an LCR meter (Agilent Technology: 4284A).
[0049] In measuring the iron loss, 15 turns of φ0.5 mm copper wire were wound around the powder magnetic core as the primary winding and 15 turns as the secondary winding. The iron loss Pcv (kW / m) was measured using a magnetic measuring device, a BH analyzer (Iwatsu Measuring Corporation: SY-8219), under the measurement conditions of a frequency of 100 kHz and a maximum magnetic flux density Bm of 100 mT. 3 ) was measured. The hysteresis loss Ph (kW / m 3 ) and eddy current loss Pe(kW / m 3 ) was calculated. Hysteresis loss Ph (kW / m 3 ) and eddy current loss Pe(kW / m 3) was performed by calculating the hysteresis loss coefficient (Kh) and eddy current loss coefficient (Ke) from the frequency curve of iron loss Pcv using the following equations (3) to (5) by the least squares method.
[0050] Pcv = Kh×f + Ke×f 2 (3) Ph = Kh × f (4) Pe = Ke × f 2 (5) Pcv: Iron loss Kh: Hysteresis loss coefficient Ke: Eddy current loss coefficient f: frequency Ph: Hysteresis loss Pe: Eddy current loss
[0051] The measurement results are shown in Table 2. Table 3 also shows the slope and intercept of the approximation line for the value obtained by subtracting the upper limit drying temperature from the decomposition onset temperature, and the slope and intercept of the approximation line for the value obtained by subtracting the lower limit drying temperature from the decomposition onset temperature.
[0052] [Table 2]
[0053] [Table 3]
[0054] As a result of intensive research, the inventors have focused on the relationship between the decomposition start temperature of the lubricant added before the coating process and the drying temperature of the insulating resin in the coating process. In particular, they have focused on the relationship between the decomposition start temperature of the lubricant and the upper and lower drying temperatures of the insulating resin. Specifically, for four types of lubricants excluding ethylene bisstearamide, which has a low initial permeability, they calculated approximation equations of "decomposition start temperature - upper drying temperature" and "decomposition start temperature - lower drying temperature" (solid lines in FIG. 1). Furthermore, as a result of intensive research, they have found that the initial permeability is improved and the hysteresis loss is reduced by using a lubricant that satisfies the following relational expressions (1) and (2), in which the intercepts of each approximation equation are ±20K (the two-dot chain line in FIG. 1 indicates the range of relational expression (1), and the one-dot chain line in FIG. 1 indicates the range of relational expression (2)). (Relationship (1)) TIFF0007623327000008.tif21145(Relationship (2)) TIFF0007623327000009.tif18145
[0055] Looking specifically at the relationship between formulas (1) and (2), of the five types of esters, lauric acid, stearic acid, fatty acid derivatives, zinc stearate, and ethylenebisstearamide, only ethylenebisstearamide does not satisfy the relationship. Specifically, the value of ethylenebisstearamide calculated based on formulas (1) and (2) is as follows: 417.864 <Th<457.864 346.755 <Tl<386.755 The upper limit drying temperature of ethylene bisstearamide shown in Table 1 is 473.15 (K) and the lower limit drying temperature is 453.15 (K), which does not satisfy the above relational formula.
[0056] Looking at ethylene bisstearamide (Comparative Examples 13 to 19), some of them have hysteresis loss and iron loss at the same level as other lubricants, but the initial permeability is low, at a maximum of about 125. Therefore, it was confirmed that if a lubricant that does not satisfy the relational expressions (1) and (2) is used, it is not possible to achieve both high permeability and low hysteresis loss, and therefore low iron loss.
[0057] It was also confirmed that even if a lubricant satisfies the above-mentioned relational expressions (1) and (2), it is not possible to achieve both magnetic permeability and low hysteresis loss, and therefore low iron loss, in relation to the drying temperature in the coating process. Specifically, it was confirmed that the drying temperature in the coating process needs to be equal to or higher than the lower limit of Tl (K) and equal to or lower than the upper limit of Th (K) calculated from the relational expressions (1) and (2).
[0058] In Examples 1 to 12, in which the drying temperature in the coating process is equal to or higher than the lower limit of Tl(K) and equal to or lower than the upper limit of Th(K) calculated from the relational expressions (1) and (2), the hysteresis loss is reduced and low iron loss is maintained compared to each comparative example using the same type of lubricant. Of particular note is the magnetic permeability of the Examples, which exceeds 140. In other words, it was confirmed that by setting the drying temperature in the coating process to equal to or higher than the lower limit of Tl(K) and equal to or lower than the upper limit of Th(K) calculated from the relational expressions (1) and (2), it is possible to achieve both high magnetic permeability and low iron loss.
[0059] (Other embodiments) In this specification, an embodiment of the present invention has been described, but this embodiment is presented as an example and is not intended to limit the scope of the invention. The above-mentioned embodiment can be implemented in various other forms, and various omissions, substitutions, and modifications can be made without departing from the scope of the invention. The embodiment and its modifications are included in the scope of the invention and its equivalents described in the claims, as well as in the scope and gist of the invention.
Claims
[Claim 1] and an insulating layer forming step of adding a lubricant and an insulating resin to the soft magnetic powder to form an insulating layer around the soft magnetic powder, The insulating layer forming step includes: a lubricant adding step of adding the lubricant to the soft magnetic powder; a coating process in which an insulating resin is added to the soft magnetic powder that has been subjected to the lubricant adding process, the insulating resin is dried, and an insulating layer is formed around the soft magnetic powder; Including, When the absolute temperature at which decomposition of the lubricant begins in a thermogravimetric differential thermal analysis is Td (K), the absolute temperature of the upper limit of the drying temperature of the insulating resin in the insulating layer forming process is Th (K), and the absolute temperature of the lower limit of the drying temperature of the insulating resin in the insulating layer forming process is Tl (K), The lubricant satisfies the following formulas (1) and (2): The upper limit absolute temperature Th of the drying temperature of the insulating resin and the lower limit absolute temperature Tl of the drying temperature of the insulating resin satisfy the conditions that the magnetic permeability is 142 or more and the hysteresis loss is 190 (kW / m 3 ) or less, The drying temperature in the insulating layer forming step is equal to or higher than the lower limit of Tl (K) and equal to or lower than the upper limit of Th (K), which are calculated from the following formulas (1) and (2): A method for producing powder for dust cores, comprising: (Formula 1) (Formula 2)
Citation Information
Patent Citations
Dust core and its manufacture
JP2000030925A
Dust core and method of manufacturing the same
JP2010114222A
Dust core and method of manufacturing the same
JP2010219159A
Dust core and method of manufacturing the same
JP2010219161A
Method of manufacturing dust core
JP2021093405A